Pengaruh Minat Belajar Siswa terhadap Hasil Belajar Trigonometri - Nadun Nadun (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
This research aims to know the influence of interest in learning mathematics achievement. The benefits of this research is to analyze the effect of minatterhadap the achievements of learning math. The methods used in this study is the analysis of the comparison with the present exposé performed on class X students in SMK Negeri 1 Cikarang Barat, Kab. Bekasi. The sample in this research totalled 67 people were taken with learners how random population of as many as 207 affordable learner people. The instruments used in the form of the now 30-grain statements and already validated in empirical. Data analysis the results of research done in a descriptive and inferensial use  "test " t, with the first test of its homogeneity and normality. Based on data processing, obtained summary there are significant effects of interest to learning achievements learning mathematics in class X students in SMK Negeri 1 Cikarang Barat, Kab. Bekasi, West Java. This can be evidenced by the acquisition value t_hitung > t_tabel  6.610 > 1.960.